Immunoinformatics-driven design of multi-epitope vaccine targeting antibiotic-resistant Salmonella typhimurium - Adnan Khan; Ayaz Ahmad; Farhad Badshah; Muhammad Ali; Muhammad Salman Khan; Warda Naz; Eliana Ibánez-Arancibia; Patricio R. De los Ríos-Escalante; Mohamed Taha Yassin (PLoS ONE, 2026)
Salmonella typhimurium , a Gram-negative bacterium, is a significant cause of gastroenteritis worldwide, with outbreaks occurring in diverse regions. Despite its global impact, there is currently no vaccine for human use against this pathogen. Complicating treatment efforts, S. typhimurium has exhibited resistance to multiple antibiotics, posing challenges to effectively managing infections. Given its prevalence and unresolved antibiotic resistance–associated global health burden, urgent attention is required to develop a genuinely effective vaccine. Using the S. typhimurium complete proteome data, vaccinomics-assisted immunoinformatics techniques were employed in the current investigation to find possible vaccine candidates. Candidate proteins were identified based on essentiality, lack of homology with the human proteome, and absence from the gut microbiome. Using a reverse vaccinology methodology, four antigenic outer membrane proteins were ranked in order of priority for lead epitope prediction. To boost immune responses against the intended vaccination, lead B and T-cell epitopes were coupled with appropriate linker and adjuvant peptide sequences to create multiepitope-based chimeric vaccines. The ST-MEVC construct was ranked according to several immunological, physicochemical, and immune receptor docking scores. Immune simulation predicted a strong immunogenic response for the proposed vaccine formulation. Molecular dynamics simulations analysis confirmed stable molecular interactions between the primary vaccine construct and the host receptors. The ST-MEVC construct’s feasible cloning potential within the E. coli expression system was anticipated by in silico restriction and cloning studies. The proposed vaccine design is expected to elicit more robust immune responses against S. typhimurium infections and will be safer, more efficacious, and more promising for investigation using in vitro/in vivo assays.